Antibacterial activity of ethanolic extracts of rhizome from three ginger varieties against acne isolated bacteria - IDA INDRAWATI; MIA MIRANTI; ISY'AINI RIFQA MAYFI (Smujo International, 2017)
Abstract. Indrawati I, Miranti M, Mayfi IR. 2017. Antibacterial activity of rhizome extracts of three ginger varieties against acne-isolated bacteria. Nusantara Bioscience 9: 92-96. Antibacterial activity of rhizome extracts of three ginger (Zingiber officinale Rosc.) varieties against bacteria isolated from acne was done. Three ginger varieties, namely emprit, gajah and red ginger, were tested to obtain the best concentration of ethanolic extracts among them in inhibiting the growth of the acne-isolated bacteria. This research used experimental approach by Completely Randomized Factorial Design with two factors of treatment, A x B. The first factor (A) were bacteria strain isolated from acne that consists of 3 levels. The second factor (B) was a varied concentration of rhizome ethanolic extract of three ginger varieties which consist of 7.5, 10, 12.5, 15, 17.5 and 20% for emprit and gajah, while for the concentration used for red were 2, 2.5, 5, 7.5, 10 and 12.5%. Moreover, a synthetic antibiotic clindamycin 30 mg mL-1 was used as a comparison. The obtained data were statistically analyzed using ANOVA with 95% of confidence and then followed by Tukey test when the significance was detected. The results showed that the acne-isolated bacteria were identified as Propionibacterium sp 1 and 2 and Staphylococcus. The rhizome ethanolic extract of red ginger had the highest antibacterial activity against the tested bacteria. This finding was supported by the fact that the red ginger variety had a small value of Minimum Inhibitory Concentration (MIC). Additionally, the measurement of clear zone revealed that the interaction between ethanolic extract of red ginger with a concentration of 12.5% ??producing a clear zone of 13.5, 25.0 and 17.5 mm against Propionibacterium sp.1, Staphylococcus sp and Propionibacterium sp.2, respectively.